Description of a New Species of Robertsmyia Bee Fly (Bombyliidae: Bombyliinae) from the South Australian mallee - Newton, Mark A; Li, Xuankun (Zootaxa, 2025)
A new species, Robertsmyia aureola sp. nov., of Bombyliinae is added to the previously monotypic genus Robertsmyia Li & Yeates, 2018. Specimens of both sexes were collected in mallee habitat from the Riverland near Cadell and Waikerie, South Australia. The generic diagnosis of Robertsmyia is revised and a key to species of the genus is provided.